2013
DOI: 10.1016/j.cmet.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

EBF2 Determines and Maintains Brown Adipocyte Identity

Abstract: Summary The master transcription factor, Pparγ regulates the general differentiation program of both brown and white adipocytes. However, it has been unclear whether Pparγ also controls fat lineage-specific characteristics. Here, we show that Early B-Cell Factor-2 (Ebf2) regulates Pparγ binding activity to determine brown versus white adipocyte identity. The Ebf DNA-binding motif was highly enriched within brown adipose-specific Pparγ binding sites that we identified by genome-wide ChIP-Seq. Of the Ebf isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
324
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(336 citation statements)
references
References 50 publications
5
324
2
5
Order By: Relevance
“…Indeed, PRDM16 directly interacts and modulates the transcriptional activities of CCAAT/enhancer-binding protein-β, PPARγ and early B-cell factor 2 and PPARγ co-activator 1α (PGC1α). 6,8,9,27 Consistent with these observations, genome-wide chromatin immunoprecipitationsequencing analysis of PRDM16 revealed that PRDM16 binding in BAT is highly enriched at the binding sites for C/EBPs, PPARs and EBFs. 28 Importantly, ectopic expression of PRDM16 and CCAAT/enhancer-binding protein-β is sufficient to convert nonadipogenic fibroblasts, such as dermal fibroblasts from mice and humans, into brown adipocytes.…”
Section: Transcriptional Regulation Of Brown and Beige Adipocyte Devesupporting
confidence: 64%
“…Indeed, PRDM16 directly interacts and modulates the transcriptional activities of CCAAT/enhancer-binding protein-β, PPARγ and early B-cell factor 2 and PPARγ co-activator 1α (PGC1α). 6,8,9,27 Consistent with these observations, genome-wide chromatin immunoprecipitationsequencing analysis of PRDM16 revealed that PRDM16 binding in BAT is highly enriched at the binding sites for C/EBPs, PPARs and EBFs. 28 Importantly, ectopic expression of PRDM16 and CCAAT/enhancer-binding protein-β is sufficient to convert nonadipogenic fibroblasts, such as dermal fibroblasts from mice and humans, into brown adipocytes.…”
Section: Transcriptional Regulation Of Brown and Beige Adipocyte Devesupporting
confidence: 64%
“…Ebf2-deficient mice develop dysmorphic fatty tissue devoid of brown-fat-specific characteristics in place of BAT (18). Thus, whereas Ebf2 is required to induce the brown-fat cell-selective gene program, it is dispensable for adipogenesis per se.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we combined lineage and cell surface markers to prospectively isolate brown preadipose cells during embryogenesis. Global mRNA transcriptomic analyses identified a brown-preadipose-specific gene signature, which included early B-cell factor 2 (Ebf2), a critical transcriptional regulator in mature brown adipocytes (18). We found that brown/beige preadipose activity in embryos and adult fat depots was restricted to Ebf2-expressing cells.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Genome-wide analyses have demonstrated that Ppar-γ binds and regulates distinct target genes in brown and white fat cells 116,117 . We recently discovered that Ebf2, a helix-loop-helix transcription factor, regulates Ppar-γ activity to drive the expression of Prdm16 and a brown fat fate 116 (Fig. 2).…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%